MDA5 against enteric viruses through induction of interferon-like response partially via the JAK-STAT cascade - Li, Yang; Wang, Wenshi (Antiviral research, 2020)
Enteric viruses including hepatitis E virus (HEV), human norovirus (HuNV), and rotavirus are causing global health issues. The host interferon (IFN) response constitutes the first-line defense against viral infections. Melanoma Differentiation-Associated protein 5 (MDA5) is an important cytoplasmic receptor sensing viral infection to trigger IFN production, and on the other hand it is also an IFN-stimulated gene (ISG). In this study, we investigated the effects and mode-of-action of MDA5 on the infection of enteric viruses. We found that MDA5 potently inhibited HEV, HuNV and rotavirus replication in multiple cell models. Overexpression of MDA5 induced transcription of important antiviral ISGs through IFN-like response, without triggering of functional IFN production. Interestingly, MDA5 activates the expression and phosphorylation of STAT1, which is a central component of the JAK-STAT cascade and a hallmark of antiviral IFN response. However, genetic silencing of STAT1 or pharmacological inhibition of the JAK-STAT cascade only partially attenuated the induction of ISG transcription and the antiviral function of MDA5. Thus, we have demonstrated that MDA5 effectively inhibits HEV, HuNV and rotavirus replication through provoking a non-canonical IFN-like response, which is partially dependent on JAK-STAT cascade.